Pemanfaatan simulasi performa desain bangunan pada proses studio arsitektur - MD Krisna Adya Anindita; Frengky Benediktus Ola; Natalia Suwarno; Nimas Sekarlangit (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Design is a unified system consists of parameters that influence each other, so design considerations must be careful. Building design performance is a measurable parameter, and integrating the planning and design process can make decision-making more focused and measurable. This paper describes the benefits and constraints of integrating building design performance simulations in the architectural studio design process using a design process of the Student Learning and Innovation Center. The study emphasizes cooling loads and daylighting using building design performance simulation to analyze the design form, layout, and building skin through shading study, UTCI, thermal comfort, wind, solar radiation, daylight, and cooling loads. Simulation using ladybug, honeybee, and sefaira software. The result is BPS utilization in the design process can assist designers in considering strategic design decisions when the problem is simple or aims to study climatic conditions. When the design problem is complex or requires detailed simulation, BPS utilization in the design process becomes more complicated so that the potential for simulation errors is more significant.